Economics : an alternative text - Routh, Guy. (London : Macmillans press, 1984)
This book arises from a long time felt discontent with orthodox texts that require students to spend an undue time mastering the models that have been thought up by past generations of theorists, and an inadequate time in exploring the world in which they live.
Includes index.
aia 25/01/2019
Loans
Keywords: Economics; Economics - alternative text